Evaluasi Total Quality Management Perspektif Deming, Juran, dan Crosby dalam Pendidikan di Pusat Kegiatan Belajar Masyarakat - Desmawati; Subandi Subandi; Deden Makbuloh; Ahmad Fauzan (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
This study aims to evaluate Total Quality Management (TQM) from the perspectives of Deming, Juran, and Crosby in improving educational quality at Pusat Kegiatan Belajar Masyarakat (PKBM). The urgency of this study is grounded in the need for PKBM, as a community-based non-formal education institution, to strengthen service quality, institutional accountability, tutor competence, stakeholder participation, and continuous improvement culture. This study employed a qualitative literature review with an evaluative-conceptual approach by synthesizing theoretical works, empirical studies, and policy-oriented literature related to TQM, quality assurance, non-formal education, and Community Learning Centres. The analysis was conducted through thematic synthesis by mapping Deming’s principles of systemic leadership and continuous improvement, Juran’s quality trilogy of planning, control, and improvement, and Crosby’s principles of conformance to requirements, prevention, and zero defects. The findings indicate that the three perspectives offer complementary contributions to PKBM quality improvement. Deming strengthens process orientation and sustainable quality culture; Juran provides a structured mechanism for quality planning, monitoring, and institutional improvement; while Crosby reinforces service consistency, administrative accuracy, and prevention of quality failure. This study concludes that TQM can serve as a contextual evaluation framework for improving PKBM governance, learning services, tutor professionalism, learner satisfaction, and stakeholder trust. The implication of this study is that PKBM managers and policymakers need to develop clearer quality standards, strengthen internal evaluation, improve tutor capacity, and institutionalize continuous improvement as the basis of non-formal education quality management.